Non-motor symptoms of Parkinson's disease - Chaudhuri, K. Ray; Tolosa, Eduardo; Schapira, Anthony H. V. (Anthony Henry Vernon); Poewe, W. ([Oxford] : Oxford University Press, 2015)
This title summarises the current understanding of non-motor symptoms in Parkinson's disease and points the way towards future research.
This edition previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2016).
Keywords: Parkinson's disease -- Complications; Parkinson's disease